DNA Display II. Genetic Manipulation of Combinatorial Chemistry Libraries for Small-Molecule Evolution - Halpin, David R; Harbury, Pehr B (PLOS Biology, 2004)
The authors use DNA "genes" to direct the synthesis of combinatorial chemistry libraries, and show in an in vitro selection experiment that specific drugs can be developed.